Designing a PMRI-Based Learning Trajectory for Algebraic Forms Using the Iftar Context - Walid, Abul; Zulkardi, Zulkardi; Putri, Ratu Ilma Indra; Susanti, Ely; Mulyono, Budi (Edumatica : Jurnal Pendidikan Matematika, 2025)
Algebra is an essential part of mathematics and is still challenging for students to understand, including algebraic forms. Difficulties concern mathematization, understanding algebraic expressions, applying arithmetic operations in numerical and algebraic expressions, understanding the concept of variables, and formulating mathematical models. The design of a Hypothetical Learning Trajectory (HLT) with PMRI learning principles that integrate the context of Iftar can assist students in understanding this algebraic form. This study aims to describe the design and implementation of HLT for learning algebraic form using the context of Iftar. The method used was design research with validation studies, consisting of three main phases: preparing for the experiment, experimenting in the classroom (pilot and teaching experiment), and conducting retrospective analysis. The subjects were 18 7th-grade students of MTs Laboratorium UIN Sultan Thaha Saifuddin Jambi. Data were collected through observation, interviews, and documentation. The results showed that learning using the context of Iftar could promote students' understanding of algebraic form, students stated a situation in algebraic form, used algebraic operations in problem solving, and provided real experience solving problems with algebra.